Digital Education for Students of LBBP D’King Study, Kramat Jati, East Jakarta - Kurniawan, Lydia; Handari, Henni; Sitanggang, Tikkos; Hidayat, Malik; Yulius, Yopie; Syahdina, Aang; Mahardini, Swesti (Journal of Community Service and Empowerment, 2024)
This community service activity was carried out in collaboration with lecturers from STIE YAI, students, and teaching staff at LBBP (Lembaga Bimbingan Belajar Pelajar) D’King Study in Kramat Jati, East Jakarta. The implementation methods included lectures, discussions, Q&A sessions, and training on the use of digital technology in learning activities as an effort to transform education and realize "Merdeka Belajar" (Freedom to Learn). The use of technology is expected to enhance the quality of learning. There are three outcomes from the discussion held during the digital education outreach activities. First, a Unified Understanding of Educational Digitalization: The participants, especially the educators at LBBP D’King Study, gained a shared understanding of strengthening educational digitalization. They are now capable of creating learning materials with the help of digital technology, making the content more engaging, communicative, and easier for students to comprehend. This, in turn, boosts the students' motivation to learn. Second, the Successful Execution of Activities: The community service activities focused on strengthening educational digitalization were well-executed and aligned with the planned objectives. Third, Follow-Up Phases Planned: After the completion of this community service, subsequent steps will be taken to maintain consistency in contributing to the advancement of educational digitalization at LBBP D’King Study in Kramat Jati, East Jakarta. These efforts are part of an ongoing commitment to improve the quality of education through technology integration.